In vitro evaluation of the hypoglycemic properties of lactic acid bacteria and its fermentation adaptability in apple juice. (January 2021) - Wang, Xiaowei; Han, Mengzhen; Zhang, Meina; Wang, Yu; Ren, Yaopeng; Yue, Tianli; Gao, Zhenpeng
Abstract: We screened for lactic acid bacteria with a hypoglycemic effect and suitable for apple juice fermentation. Among eight lactic acid bacteria, the strain with the greatest resistance to acid and bile salts, adhesion, α-glucosidase inhibitory activity, and fermentation performance was identified by principal component analysis. The adaptability of the screened strain to several varieties of apple juice was evaluated, and its growth curve in the most suitable substrate was determined. Lactobacillus fermentum 21828 demonstrated tolerance to pH 2.5 and bile salts, adhesion, α-glucosidase inhibitory activity (35.00%), and good fermentation performance, comparable to that of Lactobacillus rhamnosus GG (reference strain). Among seven apple cultivars, Aksu apple juice after fermentation by L . fermentum 21828 showed the highest viable count (3.40 × 10 8  CFU/mL) and sensory score (84.33), and its α-glucosidase inhibition dose-dependently significantly increased compared to unfermented apple juice. Its growth plateaued after 20 h, when the viable count reached 3.40 × 10 8  CFU/mL. Highlights: Lactobacillus fermentum 21828 showed probiotic properties and a hypoglycemic effect in vitro. Aksu was the most suitable fermentation substrate for Lactobacillus fermentum 21828. Aksu resulted in the highest viable count and sensory score after fermentation. α-Glucosidase inhibition by Aksu apple juice was significantly increased after fermentation. α-Glucosidase inhibition by Aksu apple juice was dose dependent.